On the formation of international migration policies when no country has an exclusive policy-setting say - Oded Stark; Alessandra Casarico; Carlo Devillanova; Silke Uebelmesser (University of Bonn, Center for Development Research (ZEF), 2011)
This paper identifies the migration policies that emerge when both the sending country and the receiving country wield power to set migration quotas, when controlling migration is costly, and when the decision how much human capital to acquire depends, among other things, on the migration policies. The paper analyzes the endogenous formation of bilateral agreements in the shape of transfers to support migration controls, and in the shape of joint arrangements regarding the migration policy and the cost-sharing of its implementation. The paper shows that in equilibrium both the sending country and the receiving country can participate in setting the migration policy, that bilateral agreements can arise as a welfare-improving mechanism, and that the sending country can gain from migration even when it does not set its preferred policy.
Keywords: F22; I30; J24; J61; 330; Human capital formation; International migration; Migration policies; Welfare analysis; Migrationspolitik; Internationale Zusammenarbeit; Internationale Wanderung; Bildungsinvestition; Zwei-Länder-Modell; Wohlfahrtsanalyse; Theorie